Impact of Artificial Intelligence on Customer Relationship Management: a Bibliometric Analysis - Aleksy Kwilinski; Nataliia Trushkina; Yuliia Remyha; Tamila Patlachuk (Proceedings of the International Conference on Applied Innovations in IT)
In modern conditions, the strategic task of logistics management of companies is to form an appropriate customer relationship management system that is able to quickly respond to crisis situations, risks, threats, transformation of the business environment, as well as flexibly adapt to unstable demand and constant changes in customer needs and preferences. In this regard, it is advisable to introduce qualitatively new management and customer-oriented approaches, smart technologies, customer experience management methods, digital marketing tools, and digital innovations. At the same time, in recent years, the use of artificial intelligence as the most influential digital innovation in customer relationship management has played a significant role. Therefore, the purpose of this article is to identify the relationship between artificial intelligence and customer relationship management by characterizing the evolution of key patterns of scientific publications on this problem. To achieve the goal, a relevant sample of scientific articles was formed based on identifying periods of publication activity and bibliometric analysis of keyword coincidences to identify promising areas of research in this area. The formed sample of publications for the study includes 797 documents indexed by the database Scopus for the period 2001-2024. Bibliometric analysis and visualization of its results were carried out using the VOSviewer software product. Based on visualization maps, seven clusters were identified and characterized by the content coincidence of keywords in publications and five stages of evolutionary development of the customer relationship management system using artificial intelligence. Based on the analysis of empirical data, an exponential growth in the number of publications on the selected issues was confirmed (the annual increase in the number of scientific papers on this topic is 15.3%). The results of the analysis can be used in further research to substantiate and develop a strategy for the digital transformation of the customer relationship management system.